2020
DOI: 10.3390/plants9111551
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Bioactive Metabolites and Biological Activities of Calli, Shoots, and Seedlings of Mertensia maritima (L.) Gray

Abstract: Mertensia maritima (L.) Gray is threatened with extinction owing to climate change, poor seed germination, and ocean warming. In vitro explant-culture is used for ex situ preservation and plantlet massive production. In vitro cell and organ cultures serve as an alternative plant material source to investigate the biological activities and phytochemical profiles of rare plants. We aimed to develop an efficient callus and shoot production protocol and investigate bioactive metabolites, antioxidants, and enzyme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…In vitro micropropagation is an effective and applicable method for preserving biodiversity and mass production of important plants [ 29 , 30 , 31 ]. The surface disinfection of in vivo plant materials is a prerequisite for initiating in vitro plant cultures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro micropropagation is an effective and applicable method for preserving biodiversity and mass production of important plants [ 29 , 30 , 31 ]. The surface disinfection of in vivo plant materials is a prerequisite for initiating in vitro plant cultures.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 6-BA, 6-furfuryladenine (6-KN), or Thidiazuron (TDZ) at 1–12 µM increased the rate of regeneration, number of shoots per K. parviflora rhizome bud, and number of roots per shoot. Cytokinins are important PGRs that can promote axillary shoot multiplication [ 29 , 31 , 40 ], somatic embryogenesis [ 41 ], and adventitious shoot regeneration [ 42 ] in numerous plants. However, the application of cytokinin often adversely affects in vitro rhizogenesis [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that plants can produce various secondary metabolites as natural antioxidants (including flavonoids and isoflavones, etc.) to protect the skin from photoaging [ 29 , 30 ]. Thus, we identified metabolites that may be correlated with their pharmacological activities in AYC-CS-E derived from A. yomena roots.…”
Section: Resultsmentioning
confidence: 99%